Overview of Specifications to the ACMG/AMP Variant Interpretation Guidelines. (8th August 2019) - Harrison, Steven M.; Biesecker, Leslie G.; Rehm, Heidi L.
Abstract: The 2015 ACMG/AMP guidelines established a classification system for sequence variants; however, the broad scope of these guidelines necessitates specification of evidence types for specific genes or diseases of interest. Since publication of the guidelines, both general use and disease‐focused specifications have emerged to aid in accurate application of ACMG/AMP evidence types. This article summarizes the approaches to, and rationale for, specifying three evidence categories (population frequency data, variant type and location, and case‐level data), including available resources and a quantitative framework that can inform the specification process. © 2019 by John Wiley & Sons, Inc.